1982
DOI: 10.1159/000182723
|View full text |Cite
|
Sign up to set email alerts
|

Renal Scintigraphy versus Renal Vein Renin Activity for Identifying and Treating Renovascular Hypertension

Abstract: This paper compares renal scintigraphy (RS) with renal vein renin activity (RVRA), intravenous pyelography (IVP), and peripheral plasma renin activity (pPRA) in a population of hypertensive subjects with suspect renovascular hypertension (RVH), of whom 30 underwent surgery, in order to evaluate (a) screening ability of RS for RVH, and (b) surgical prognosis of RS for RVH. RS agreed with arteriographic findings of arterial stenosis in 91% of patients and proved more sensitive as a screening test than IVP and pP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…27 As far as ACE inhibitor scintigraphy is concerned there are many studies available which are shown in Table 1, but yet there is no consensus on scintigraphy protocol including radiopharmaceutical, sequence of studies, ACE inhibitors, their dose and specific criteria. [8][9][10][11][12][13][14][15][16][17][18][19][20] Nally JV et al achieved the sensitivity and specificity of 100% and their criteria for positive test were decrease in maximum activity, delayed uptake, widening of peak activity and slowing the excretory phase. 12 But on contrary , Kumar r et al and Orellana P et al showed lower sensitivity of 44.4% and 60.9% respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 As far as ACE inhibitor scintigraphy is concerned there are many studies available which are shown in Table 1, but yet there is no consensus on scintigraphy protocol including radiopharmaceutical, sequence of studies, ACE inhibitors, their dose and specific criteria. [8][9][10][11][12][13][14][15][16][17][18][19][20] Nally JV et al achieved the sensitivity and specificity of 100% and their criteria for positive test were decrease in maximum activity, delayed uptake, widening of peak activity and slowing the excretory phase. 12 But on contrary , Kumar r et al and Orellana P et al showed lower sensitivity of 44.4% and 60.9% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1 A large list of studies is available in the literature regarding the role of renal scintigraphy with Tc99m-DTPA and with other radioactive pharmaceutical agents, with or without captopril in screening and diagnosing patients with RAS with variable and concontrdictory results. [8][9][10][11][12][13][14][15][16][17][18][19][20] The exact role and accuracy of this investigation in screening of the patients with RAS is not established. With rapid advance in technique and radiotracer in nuclear medicine, there is need to find a suitable screening method for diagnosis of RAS.…”
Section: Introductionmentioning
confidence: 99%
“…3, 4, and 5 minutes after rapid injec¬ tion of contrast, this delayed appear¬ ance might be missed. (Thornbury and co-workers,3' for example, report that films were recorded at the end of injection [usually [10][11][12][13][14][15] s] and at 2, 3, and 5 minutes.) Third, the degree of stenosis required for the diagnosis of RAS is variable in the literature, with Rufener et al40 accepting a greater than 30% stenosis, Thornbury and colleagues33 requiring greater than 50% stenosis, and many not providing this information at all.4M3 Finally, while some studies clearly describe the frequency of unilateral vs bilater¬ al RAS in their series,2230 this infor¬ mation is not usually available.…”
Section: Intravenous Pyelogrammentioning
confidence: 99%
“…A rapid, non-invasive, reliable screening test for the presence of a renovascular cause of hypertension is necessary. Currently computerized nuclear renography (CNR) with reported sensitivity approximately 86% and specificity 89% (McAfee et al 1977;Arlart et al 1979;Chiarini et al 1982) is used in our unit.…”
Section: Introductionmentioning
confidence: 99%